PENGARUH SOCIAL MEDIA MARKETING ACTIVITIES (SMMA) TERHADAP BRAND EQUITY SERTA DAMPAKNYA PADA E-WOM DAN KOMITMEN RELASIONAL - dahlan, divankaamelia; Alimuddin Rizal Rivai (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the effect of Social Media Marketing Activities (SMMA) on Brand Equity and Its Impact on E-WOM and Relational Commitment to Scarlett Whitening's customers. The primary data in this study used a questionnaire and the secondary data was obtained through a literature search. The sample in this study was 115 which were distributed online via google form to Scarlett Whitening customers. The sampling technique in this study used purposive sampling. This study was analyzed through Partial Least Square- Structural Equation Modeling (PLS-SEM), with two tests, namely the measurement model and the structural model. The results of this study indicate that SMMA has a positive and significant effect on Brand Awareness and Brand Image. Brand Awareness has a positive and significant effect on E-WOM. Brand Awareness has a positive and insignificant effect on Relational Commitment. Brand Image has a positive and significant effect on E-WOM and Relational Commitment.